Enhancing High School Mathematics Learning Through Moodle Feature Development - Muhamad Ali Misri; Herlinda Nur’afwa Sofhya; Farouk Imam Arrasyid (MASI Mandiri Edukasi, 2025)
The development of information and communication technology in the 21st century spurs the need for digital learning systems to improve the quality of education. This research aims to develop a Learning Management System (LMS) Moodle with additional features that support mathematics learning at the high school level. The research method used in this research is the research and development (R&D) method, with the model used being the Four-D Model or adapted into a 4-D model. Based on the research results, the features developed include typing mathematical formulas using MathType by Wiris, graph visualization, and GeoGebra-based simulations. The results of the trial show that this additional feature increases the effectiveness of mathematics learning and the efficiency of students' learning time. Developing an LMS with interactive features supports a more dynamic and meaningful learning process.